Analysis of Understanding Mathematical Concepts in Junior High School Students on Integer Operation Material - Erieza Dwi Pratiwi; Ali Shodikin (UJMC (Unisda Journal of Mathematics and Computer Science), 2022)
This study aims to determine the conceptual understanding of students in junior high school in solving historical problems. The subjects of this study were students of Class VII Lamongan. The method used in this research is qualitative. Data collection techniques used are test and interview techniques. After the tests and interviews, there was 1 student with good grades, 2 students with good grades, and 1 student with bad grades, the average was 70%. Students with good category understanding can represent a concept in various mathematical representations, reformat a concept, and classify objects according to certain properties according to the concept. Eligible students can represent a concept in various mathematical representations and reformat a concept. And low-ability students can only present concepts in various forms of mathematical representation. Abstrak Penelitian ini bertujuan untuk mengetahui pemahaman konseptual siswa sekolah menengah pertama dalam menyelesaikan masalah sejarah. Subjek penelitian ini adalah siswa Kelas VII Lamongan. Metode yang digunakan dalam penelitian ini adalah kualitatif. Teknik pengumpulan data yang digunakan adalah teknik tes dan wawancara. Setelah dilakukan tes dan wawancara, terdapat 1 siswadengan nilai baik, 2 siswa dengan nilai baik dan 1 siswa dengan nilai buruk, rata-ratanya adalah 70%. Siswa dengan pemahaman kategori yang baik dapat merepresentasikan suatu konsep dalam berbagai representasi matematis, memformat ulang suatu konsep, dan mengklasifikasikan objek menurut sifat-sifat tertentu sesuai dengan konsep tersebut. Siswa yang memenuhi syarat dapat merepresentasikan suatu konsep dalam berbagai representasi matematis dan memformat ulang suatu konsep. Dan siswa berkemampuan rendah hanya dapat menyajikan konsep dalam berbagai bentuk representasi matematis.